2009
DOI: 10.3945/jn.108.097089
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Breast-feeding and Adiposity in Adult Life

Abstract: Few studies have examined whether the duration of breast-feeding is associated with BMI in adult life. In the past, the heights and weights of infants and the duration of breast-feeding were routinely recorded at infant welfare clinics in Helsinki, Finland. Most infants in the city were taken to these free clinics. The Helsinki Birth Cohort comprises 13,345 people born in the city during 1934-1944; 84% were breast-fed. In 2001, a questionnaire was sent to members of the cohort asking about their weight and hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 19 publications
3
50
0
1
Order By: Relevance
“…36 In this study, subjects who were breastfed for more than 25 days had lower FM, but actual breastfeeding p25 days was not associated with body composition after adjustment. This highlighted there might be a duration-dependent effect of breastfeeding on FM and %BF of adolescents, consistent with recent evidence suggesting a longer period of breastfeeding was associated with lower BMI at 1 year of age, 37 and that breastfeeding remained a significant protective factor up to age 5 to 6 y. 38,39 Our results supported this hypothesis and suggested the inverse association between duration of breastfeeding and obesity might be a long term effect.…”
Section: Discussionsupporting
confidence: 81%
“…36 In this study, subjects who were breastfed for more than 25 days had lower FM, but actual breastfeeding p25 days was not associated with body composition after adjustment. This highlighted there might be a duration-dependent effect of breastfeeding on FM and %BF of adolescents, consistent with recent evidence suggesting a longer period of breastfeeding was associated with lower BMI at 1 year of age, 37 and that breastfeeding remained a significant protective factor up to age 5 to 6 y. 38,39 Our results supported this hypothesis and suggested the inverse association between duration of breastfeeding and obesity might be a long term effect.…”
Section: Discussionsupporting
confidence: 81%
“…Exclusive breastfeeding and/or longer duration of breastfeeding have been associated with decreased rates of childhood obesity in many but not all studies [20][21][22][23][24][25], although the mechanisms of action have not been clearly delineated. USDA mandated WIC breastfeeding support programs, which include peer counseling, are intended to increase breastfeeding initiation, exclusivity, and duration, and are an important component of the revised WIC program in NYS.…”
Section: Discussionmentioning
confidence: 97%
“…In a systematic review by Arenz et al (20) which included 69 000 participants, the authors concluded that breast-feeding has a small, consistent, protective effect against obesity. More recently Table 2 Age distribution of overweight (OW), obesity (OB) and normal weight (N) among the study subjects: children randomly selected from eight primary and secondary schools from rural and urban areas of Thessaloniki, northern Greece Boys Girls OW (n 57) OB (n 42) N (n 99) OW (n 58) OB (n 48) N (n 106) O'Tierney et al (21) reported that breast-feeding for ,2 months might be deleterious and was associated with increased BMI. In another study, Moschonis et al (10) examined the effects of breast feeding on obesity in 2374 Greek children aged 1-5 years, concluding that children who were exclusively breast-fed were 0?49 and 0?54 times less likely to be overweight at 6 and 12 months of age, respectively, than children who were exclusively formula-fed.…”
Section: Discussionmentioning
confidence: 99%